The Effect of Fair Disclosure Regulation on Timeliness and Informativeness of Earnings Announcements - Park, Y.; Song, I.; Yang, D.; Hossain, Mahmud; Koo, J. (Elsevier, 2013)
This paper examines the effect of Korea’s fair disclosure regulation on the timeliness and informativeness of earnings announcements. The present regulation for Korean listed firms requires that if a company’s sales revenue, operating income (or loss) and net income (or loss) have changed by over 30% compared to the prior year, the firm must disclose this information through a preliminary financial report (PFR) even before the company is audited by external auditors. To analyze the effects of this policy, we first investigate the timeliness of preliminary financial report disclosures. We examine the extent to which Korean listed companies actually comply with the requirement for prompt notification of information concerning material changes in financial performance. Second, we investigate the informativeness of preliminary financial reports by analyzing differential stock market reactions to different timings of preliminary financial report disclosures. Our empirical results reveal that more than half of our sample firms release their preliminary financial reports after external audits are completed, thereby potentially invalidating the effectiveness of the regulation. In addition, we find that preliminary financial reports have information value only if they are disclosed prior to annual audit report dates. This finding supports the notion that timeliness increases the informativeness of preliminary financial report disclosure by curbing insiders’ ability to potentially profit from their information advantage.